2011
DOI: 10.1007/s10584-011-0364-6
|View full text |Cite
|
Sign up to set email alerts
|

Holocene vegetation and climate history at Haligu on the Jade Dragon Snow Mountain, Yunnan, SW China

Abstract: This paper uses pollen analysis to investigate and document the changing climate and vegetation during the Holocene based on a 400 cm core in depth obtained at a wetland site at Haligu (3,277 m a. s. l.) on the Jade Dragon Snow Mountain in Yunnan, China. By applying the Coexistence Approach to pollen data from this core, a quantitative reconstruction of climate over the last 9,300 years was made based on each pollen zone and individual core sample, which reveals the temperature and precipitation change frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…Lignin biomarker and isotopic records (Tareq et al, 2011) and pollen assemblages (Yang et al, 2005;Shen et al, 2006a) from Erhai Lake, vegetation history from Dianchi Lake (Sun et al, 1986) and various multi-proxy records from Shudu Lake (Cook et al, 2013) all point to a strong summer monsoon and wet climate during the Early Holocene. However, pollen assemblages from Haligu wetland on the Jade Dragon snow mountain (Song et al, 2012) indicate that the climatic optimum extended from 8700 to 2400 cal a BP. This long interval of optimum climate may not only pertain to a strong summer monsoon but may also be related to temperature changes.…”
Section: Evolution Of Ism Over the Last 8500 Yearsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lignin biomarker and isotopic records (Tareq et al, 2011) and pollen assemblages (Yang et al, 2005;Shen et al, 2006a) from Erhai Lake, vegetation history from Dianchi Lake (Sun et al, 1986) and various multi-proxy records from Shudu Lake (Cook et al, 2013) all point to a strong summer monsoon and wet climate during the Early Holocene. However, pollen assemblages from Haligu wetland on the Jade Dragon snow mountain (Song et al, 2012) indicate that the climatic optimum extended from 8700 to 2400 cal a BP. This long interval of optimum climate may not only pertain to a strong summer monsoon but may also be related to temperature changes.…”
Section: Evolution Of Ism Over the Last 8500 Yearsmentioning
confidence: 99%
“…In particular, palynological data can be used to reconstruct the regional vegetation and climate (Davis, 1969;Peyron et al, 2005), and have previously been shown to document monsoon evolution in China (Zhao et al, 2009). During the last few decades, a substantial amount of palaeoenvironmental research has been conducted in the Yunnan Plateau, mainly concerned with regional vegetation and climate reconstructions (Sun et al, 1986;Yu et al, 1990;Hodell et al, 1999;Shen et al, 2006a;An et al, 2011;Wang et al, 2012;Song et al, 2012;Cook et al, 2013;Xiao et al, 2014). However, the results of these previous studies remain the subject of debate and the regional patterns of Holocene vegetation history and climate changes in the region are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, the mountains of Southwest China (MSWC) has served as refugia and enabled the survival of species during globally decreasing temperatures due to the relative stability of its local climate. The distribution of many species, for example Juniperus przewalskii (Zhang, Chiang, George, Liu, & Abbott, 2005), Picea crassifolia (Meng et al, 2007) and Abies species (Song et al, 2012) on the Qinghai-Tibet Plateau (QTP) is also closely related to the retreat or advancement of glaciers and the existence of refugia in MSWC. Additionally, mountains with a substantial elevation range offer short-distance corridors for the migration of species at a vertical gradient, and these species can recolonize when the temperature becomes more suitable again (Qiu, Fu, & Comes, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al, 2006;J. Shen et al, 2005;Song et al, 2012;Sun et al, 2015;Xiao et al, 2014a). Among the numerous records, stalagmites can be accurately and precisely dated using U-series methods (Cheng et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Pollen analysis has been widely used to reconstruct Holocene paleovegetation and paleoclimate in the region (Chen et al, 2014;Cook et al, 2013;Jarvis, 1993;Kramer et al, 2010;C. Shen et al, 2006;Song et al, 2012;Xiao et al, 2014a). However, in most of these records the chronology is based on radiocarbon dating of bulk organic matter and/or is of low resolution.…”
Section: Introductionmentioning
confidence: 99%